Health Behavior in School-Aged Children (HBSC), 2005-2006 - Iannotti, Ronald J. ([Verlag nicht ermittelbar], 2012)
Since 1982, the World Health Organization (WHO) Regional Office for Europe has sponsored a cross-national, school-based study of health-related attitudes and behaviors of young people. These studies, generally known as Health Behavior in School-Aged Children (HBSC), are based on independent national surveys of school-aged children in more than 40 participating countries. The HBSC studies were conducted every four years since the 1985-1986 school year. The data available here are from the results of the United States survey conducted during the 2005-2006 school year. The study results can be used as stand-alone data, or to compare with the other countries involved in the international HBSC. The HBSC study has two main objectives. The first objective is to monitor health-risk behaviors and attitudes in youth over time to provide background data and to identify targets for health promotion initiatives. The second objective is to provide researchers with relevant information in order to understand and explain the development of health attitudes and behaviors through early adolescence. The study contains questions dealing with many types of drugs such as tobacco, alcohol, marijuana, and other substances. Other topics include questions about family composition, the student's physical health, and other health behaviors and attitudes. Some of these topics include eating habits, dieting, physical activity, body image, health problems, and bullying. A school administrator also completed a survey concerning the school's programs and policies that affect students' health and the content of various health courses.